2013
DOI: 10.1088/0268-1242/28/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phase segregation in sol–gel derived ZnMgO thin films

Abstract: Highly c-axis-oriented Zn 1-x Mg x O multilayered thin films have been deposited on p-type Si substrates with different concentration of Mg (x = 0.00−0.40) using a sol-gel spin-coating technique. The x-ray diffraction (XRD) shows that single-phase wurtzite thin films start showing phase segregation for a Mg content of x = 0.25 for the sol-gel-derived ZnMgO thin films. The element specific near edge x-ray fine structure (NEXAFS) collected at O K-edge also clearly evidence the phase segregation at x = 0.25. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…33 As a result, the ternary alloy Zn 1−x Mg x O exhibits a sensitive structurecomposition dependence, adopting the wurtzite (B4) form only for low Mg concentrations (x < 0.33). [43][44][45] Nevertheless, metastable structures of wurtzite Zn(Mg)O with very high Mg concentration can be achieved by epitaxial growth on high-quality ZnO crystals. This way, samples with Mg concentrations as high as 60% or more have been demonstrated.…”
Section: Methods and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…33 As a result, the ternary alloy Zn 1−x Mg x O exhibits a sensitive structurecomposition dependence, adopting the wurtzite (B4) form only for low Mg concentrations (x < 0.33). [43][44][45] Nevertheless, metastable structures of wurtzite Zn(Mg)O with very high Mg concentration can be achieved by epitaxial growth on high-quality ZnO crystals. This way, samples with Mg concentrations as high as 60% or more have been demonstrated.…”
Section: Methods and Structurementioning
confidence: 99%
“…28 Electronically, the Mg concentration serves to tune the Zn(Mg)O band gap gradually between that of wurtzite ZnO and MgO. 33,[43][44][45] The band gap of Zn 1−x Mg x O for a given x can be estimated from the Vegard's law E…”
Section: Methods and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…With increasing the Mg content, both the enhancement [3][4][5] and weakening [6,7] of the visible emission intensity were observed. In [3][4][5][6]8], the shift of defect-related emission band toward the short wavelength side as a result of alloying ZnO with MgO was found, whereas in [9,10] any change of emission band shape or peak position was not observed. In [11], it was shown that self-activated defect-related emission in sol-gel MgZnO phosphors can be shifted from the orange to green-blue spectral region by changing the annealing temperature and gas ambient.…”
Section: Introductionmentioning
confidence: 97%
“…The thermodynamic limit solid solubility of MgO in ZnO is reported around 4 % in the bulk [13]. However, the limit solid solubility of MgO in ZnO for thin films has been reported to be around 33 mol % as deposited by pulsed laser deposition (PLD) technique [6], 25 % as deposited by sol-gel spin-coating technique [14] and 43 % as deposited by molecular beam epitaxy (MBE) [15].…”
Section: Introductionmentioning
confidence: 99%